The M2 muscarinic receptors are essential for signaling in the heart left ventricle during restraint stress in mice - Tomankova, Hana; Valuskova, Paulina; Varejkova, Eva; Rotkova, Jana; Benes, Jan; Myslivecek, Jaromir (Stress (Amsterdam, Netherlands), 2015)
We hypothesized that muscarinic receptors (MRs) in the heart have a role in stress responses and thus investigated changes in MR signaling (gene expression, number of receptors, adenylyl cyclase (AC), phospholipase C (PLC), protein kinase A and C (PKA and PKC) and nitric oxide synthase [NOS]) in the left ventricle, together with telemetric measurement of heart rate (HR) in mice (wild type [WT] and M2 knockout [KO]) during and after one (1R) or seven sessions (7R) of restraint stress (seven mice per group). Stress decreased M2 MR mRNA and cell surface MR in the left ventricle in WT mice. In KO mice, 1R, but not 7R, decreased surface MR. Similarly, AC activity was decreased in WT mice after 1R and 7R, whereas in KO mice, there was no change. PLC activity was also decreased after 1R in WT and KO mice. This is in accord with the concept that cAMP is a key player in HR regulation. No change was found with stress in NOS activity. Amount of AC and PKA protein was not changed, but was altered for PKC isoenzymes (PKCα, β, γ, η and ϵ (increased) in KO mice, and PKCι (increased) in WT mice). KO mice were more susceptible to stress as shown by inability to compensate HR during 120 min following repeated stress. The results imply that not only M2 but also M3 are involved in stress signaling and in allostasis. We conclude that for a normal stress response, the expression of M2 MR to mediate vagal responses is essential.
Keywords: exprese genu; srdeční komory; Gene Expression; Receptor, Muscarinic M2; receptory muskarinové; Mice, Knockout; AMP cyklický; stress; Restraint, Physical; phospholipase C; Cyclic AMP; muscarinic receptors; srdce; fosfolipasy typu C; psychický stres; Heart Rate; signální transdukce; receptor muskarinový M2; srdeční frekvence; proteinkinasa C; fyzické omezení; Signal Transduction; Cyclic AMP-Dependent Protein Kinases; myši knockoutované; heart; adenylátcyklasy; Animals; zvířata; Nitric Oxide Synthase; synthasa oxidu dusnatého; Stress, Psychological; myši; Type C Phospholipases; protein kinase C; Adenylyl cyclase; Heart Ventricles; Receptors, Muscarinic; Adenylyl Cyclases; proteinkinasy závislé na cyklickém AMP; Mice; Heart; Protein Kinase C